Empowered by Intertwined Theory and Practice – Experiences From a Diabetes Sports Camp for Physically Active Adults With Type 1 Diabetes - Mattsson, Stig; Adolfsson, Peter; Jendle, Johan; Bengtsson, Viktor; Sparud-Lundin, Carina (Frontiers in Clinical Diabetes and Healthcare, 2021)
Aims: This study aimed to describe the experiences of participating in diabetes sports camps for individuals with diabetes type 1 (T1D) and how acquired knowledge could be used in daily self-management. Methods: Semi-structured telephone interviews were conducted with 15 adults with T1D. A strategic sample procedure was chosen. The interviews were analysed using qualitative content analysis. Results: An overarching theme emerged: Empowered by intertwined theory and practice, which included three main categories: Learning in a motivation-enhancing environment, Incorporation of new habits and Perceptions of glycemic control and health-related outcomes. The participants considered the camp to be an excellent opportunity to share feelings, ideas, and knowledge. They felt empowered by the camp atmosphere and the supportive environment, which created unique conditions to put theory into practice. After the camp, the general well-being was improved by incorporating new habits. Moreover, improvements in glucose control lead to the feeling of more “energy” during the training sessions but also in everyday life. Conclusions: A diabetes sports camp constitutes an excellent complimentary support in diabetes care and provides good opportunities for T1D individuals to become more independent and autonomous and thus be able to live a more satisfying life with diabetes and physical activity.